Fast determination of ethylene glycol, 1,2-propylene glycol and glycolic acid in blood serum and urine for emergency and clinical toxicology by GC-FID - Hložek, Tomáš; Bursová, Miroslava; Čabalaa, Radomír (Talanta, 2014)
A simple, cost effective, and fast gas chromatography method with flame ionization detection (GC-FID) for simultaneous measurement of ethylene glycol, 1,2-propylene glycol and glycolic acid was developed and validated for clinical toxicology purposes. This new method employs a relatively less used class of derivatization agents - alkyl chloroformates, allowing the efficient and rapid derivatization of carboxylic acids within seconds while glycols are simultaneously derivatized by phenylboronic acid. The entire sample preparation procedure is completed within 10 min. To avoid possible interference from naturally occurring endogenous acids and quantitation errors 3-(4-chlorophenyl) propionic acid was chosen as an internal standard. The significant parameters of the derivatization have been found using chemometric procedures and these parameters were optimized using the face-centered central composite design. The calibration dependence of the method was proved to be quadratic in the range of 50-5000 mg mL(-1), with adequate accuracy (92.4-108.7%) and precision (9.4%). The method was successfully applied to quantify the selected compounds in serum of patients from emergency units.
Keywords: Chromatography, Gas; Female; Ethylene Glycol; ženské pohlaví; ethylenglykol; urgentní zdravotnické služby; lidé; sérum; Glycolates; propylenglykol; Emergency Medical Services; studie případů a kontrol; Male; Case-Control Studies; chromatografie plynová; Propylene Glycol; Serum; mužské pohlaví; plamínková ionizace; Flame Ionization; toxikologie; glykoláty; Toxicology; Humans